MULTIPLANNING OF THE METHOD OF THE INTERLINGUAL COMPARATIVE ANALYSIS OF THE RELATED / UNRELATED LANGUAGES - Korbozerova , Nina (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
In the era of globalization and the expansion of language contacts, the interest of linguists in typological studies of related and unrelated languages is growing, which allows to reveal and clarify the national picture of the world in any language. In the field of comparative research, linguistics of the 21st century is characterized by the differentiation of the directions. When conducting a comparative analysis of languages, scientists use the following basic methods that have become traditional: comparative-historical, comparative, typological, contrastive. Recently, the latest research methods have been added to them, thanks to which the comparison of languages turns into a deeper, brighter and multifaceted one. First of all, it concerns areal typology and taxonomic typology. Comparative-historical linguistics studies genetically related languages in a diachronic aspect. In the 19th century, this direction is associated with the names of F. Bopp, J. Grimm, R. Raskov, A. Meillet, and F. Dietz. The goal of research in comparative-historical linguistics is the reconstruction of ancient platforms common to all related languages. In this direction, the indisputable achievement of the Romanistic school of F. Dietz is the discovery of Romano-Latin archetypes. The kinship of the languages of the world is established according to the main feature of their common origin, which makes it possible to classify languages into families/subfamilies, branches, groups and directly into languages. At the same time, accidental coincidences and lexical borrowings are not taken into account. A language family is a basic language structure, according to which closely related and distantly related languages are defined. Languages that make up one language family have common features, are the result of one language that historically preceded them, and belong to the group of related languages. This gives rise to the concept of the genealogical tree of languages and the concept of linguistic divergence. Related languages are considered variants of one continuous language tradition, different in time and space. An example is the Indo-European family of languages that share a common language, or proto-language (Indo-European). Within related languages, subgroups are distinguished, which include languageы that are closest in origin (for example, Spanish and Italian languages). In turn, languages that belong to different groups of the same family are distantly related (eg, Ukrainian and Spanish). The group of unrelated languages consists of languages that originate from different protolanguages and belong to different language families. Linguistic, or comparative, typology arose within the framework of comparative-typological linguistics and is associated with the names of A. Schlegel, A. Schleicher, V. Humboldt. Thanks to the research of representatives of the school of linguistic typology, the question of the type of language was first raised and resolved. __________ • Live Journal, https://p-tashka.livejournal.com • Korunets, I. Contrastive Typology of the English and Ukrainian Languages (Vinnitsya, 2004). • Kovtun, V. Contrastive grammar of assessment: Problems of interpretation of key terms, https://www.philol.vernadskyjournals.in.ua › part_2 • Kochergan, P. General linguistics (2006), https://irbis-nbuv.gov.ua • Methods of linguistic research: study guide, compiled by A. Tsymbal (Uman: Visavy, 2019), 106, http://oldconf.neasmo.org.ua • Selivanova, Fundamentals of modern linguistic methodology. Scientific conferences, http://oldconf.neasmo.org.ua • Selivanova, O. Modern linguistics: trends and problems: a textbook (Poltava: Dovkillya-K, 2008), 712. • Fedorenko, I., Sukhorolska, S. M., Ruda, O. V. Fundamentals of linguistic research: Textbook (Lviv: Ivan Franko LNU Publishing Center, 2009), 296.